2020
DOI: 10.3390/su12135313
|View full text |Cite
|
Sign up to set email alerts
|

Radon Concentrations in Raw Water and Treated Water Used for Bottled Water in South Korea

Abstract: Radon concentrations in the raw water and treated water used for 59 brands of bottled water produced in South Korea were analysed. The radon levels in 59 raw water samples ranged from 3.7 to 476.8 Bq/L, with a geometric mean of 49.0 Bq/L. The mean radon levels in raw water samples were high in Jurassic granite aquifers and low in volcanic rock aquifers. However, the maximum radon levels were observed in metamorphic rock aquifers. The concentrations in 55 treated water samples ranged from 0.1 to 239.4 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Since no prior radon concentration results are available for coconut water, a qualitative comparison may be made from studies of radon in water. Akar et al [46] reported lower values of radon concentration in tap water versus well water and Cho et al [47] observed a 16.0% -98.9% decrease in the radon concentration between raw water and treated water in their study of bottled water.…”
Section: Resultsmentioning
confidence: 93%
“…Since no prior radon concentration results are available for coconut water, a qualitative comparison may be made from studies of radon in water. Akar et al [46] reported lower values of radon concentration in tap water versus well water and Cho et al [47] observed a 16.0% -98.9% decrease in the radon concentration between raw water and treated water in their study of bottled water.…”
Section: Resultsmentioning
confidence: 93%
“…only the surface water sources mean value of 9.3 BqL − 1 is below this level; however, most of the area's inhabitants use the bore and spring water for drinking. Therefore, it is recommended that drinking water not be used before proper treat meant like granular activated carbon (GAC) (Cho et al 2020). The other conventional method is not using the water for drinking purpose immediately taken out from the bore or spring and leaving it unexposed for few days so that radon activity decreases as being half-life of radon 3.82 days after rst half-life enough radon decayed.…”
Section: Discussionmentioning
confidence: 99%
“…Those samples of water for which in eld measurement are not possible by one or other reason and the measurement to be taken in the laboratory take more than 10 hours from collection to the laboratory. In such cases, the measurement is corrected by using the term decay conversion factor (DCF), by using equation (Ali et al 2010, Cho et al 2020):…”
Section: Methodsmentioning
confidence: 99%